Sistem Pakar Pendeteksian Varicella Simplex Dengan Menggunakan Teorema Bayes - Puji Sari Ramadhan (JURIKOM (Jurnal Riset Komputer), 2018)
Varicella Simplex is one of the infectious diseases that attacks the skin, this disease is caused by infection with the Varicella Zoster virus. In general, the detected virus can attack humans through systemic properties that cause overall infection. Most of this disease is suffered by people living in areas that are humid and whose immune systems are weak. At this time the lack of information and knowledge about Varicella Simplex resulted in the difficulty of knowing the disease early so that it could cause early treatment problems that could lead to greater transmission of the disease. Based on the phenomenon that has been stated, it requires a technology that is able to provide the right knowledge and information about Varicella Simplex along with the symptoms that occur in society, namely by applying Expert System technology which is part of the Artificial Intelligence science which will be implemented into a system computer-based using the Bayes Theorem application, so that later it can be used to diagnose or detect Varicella Simplex disease and can be used as a health consultation service that can help health experts as part of the initial diagnosis reference